2014
DOI: 10.5317/wjog.v3.i2.71
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gynecologic oncologist availability on ovarian cancer mortality

Abstract: AIM To determine the association between the distribution of gynecologic oncologist (GO) and population-based ovarian cancer death rates. MATERIALS AND METHODS Data on ovarian cancer incidence and mortality in the United States (U.S.) was supplemented with U.S. census data, and analyzed in relation to practicing GOs. GO locations were geocoded to link association between county variables and GO availability. Logistic regression was used to measure areas of high and low ovarian cancer mortality, adjusting for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…63,64 Among children, long travel times to a treatment center is associated with significant negative financial and social impacts on patients and families. 31 Our results suggest that, among adolescents, socioeconomic factors, such as poverty and health insurance coverage, may have a greater impact on cancer mortality than geographic distance to treatment facility.…”
Section: Discussionmentioning
confidence: 99%
“…63,64 Among children, long travel times to a treatment center is associated with significant negative financial and social impacts on patients and families. 31 Our results suggest that, among adolescents, socioeconomic factors, such as poverty and health insurance coverage, may have a greater impact on cancer mortality than geographic distance to treatment facility.…”
Section: Discussionmentioning
confidence: 99%
“…While this may be the case, geographic disparities in ovarian cancer care have been well documented, 6,1113 and these are likely to remain an issue for some ovarian cancer patients. A recent study in one urban National Cancer Institute-designated cancer center showed that the farther gynecologic cancer patients were required to travel to get to treatment (those traveling above 10, but less than 50 miles), the less likely they were to complete recommended care.…”
Section: Discussionmentioning
confidence: 99%
“…35 However, there is variable uptake of this recommendation, which may be due in part to the uneven distribution of these subspecialists across the United States and general lack of availability in rural areas where many ovarian cancer patients reside 3,6 or lack of physician referral. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Rural ovarian cancer patients have been shown to have less access to specialty surgical care and treatment once they are diagnosed with cancer. 4,[14][15][16][17][18][19] Additionally, they may have less access to diagnosing physicians. Undiagnosed women with ovarian cancer often need the skills of a perceptive primary care physician to discriminate their symptoms, which can be nonspecific and present months to years before a patient is diagnosed.…”
Section: Introductionmentioning
confidence: 99%